Technical Advisory Committee on Pharmaceutical Assistance of the Regional Intermanagers Commission Trans-Amazon and Xingu of Pará: Experience report (Research, Society and Development, 2023)
Introduction: A Pharmaceutical Assistance Technical Committee is a body or group of health professionals, usually pharmacists, whose main objective is to promote the management and control of aspects related to pharmaceutical assistance in each context, such as in a healthcare institution. health, municipality, state, or country. Pharmaceutical assistance refers to the set of actions aimed at ensuring access, safety, effectiveness, and rational use of medicines by the population. Objective: To contextualize the process of agreement and implementation of the Technical Advisory Committee for Pharmaceutical Assistance in the Trans-Amazonian and Xingu Regional Inter-Management Commission, in the state of Pará. Method: Experience report based on Action Research. Conclusion: The Pharmaceutical Assistance Technical Advisory Committee of the Transamazônica and Xingu Regional Intermanager Commission, in the state of Pará, meets the need to deepen the dialogue on topics related to access, quality use and sustainability of Pharmaceutical Assistance in the field of public health.